2010
DOI: 10.1108/13527601011016907
|View full text |Cite
|
Sign up to set email alerts
|

Stress and psychological well‐being in UK and Malaysian fire fighters

Abstract: Purpose-The purpose of this paper is to examine the relationship among sources of stress, coping strategy, job satisfaction and psychological well-being and to examine the roles of coping behaviour as the moderator variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…It also means that interaction of KE and IE contributes 75.2% of IP while the remaining 24.8 % is explained by other factors not captured in this study. The findings are consistent with those of Malek, Mearns and Dahlan A. Malek, Mearns, & Flin (2010) who found that hierarchical moderated multiple regression can be used to find out whether two sets of independent variables contributes to an increase in dependent variable by testing for changes in R square. Multiple regression has shown that openness, autonomy, integration and experimentation capacities have a significant influence on IP (Chang, Chang, Chi, Chen, & Deng, 2012).…”
Section: A Normality Test Of Ke and Ipsupporting
confidence: 90%
“…It also means that interaction of KE and IE contributes 75.2% of IP while the remaining 24.8 % is explained by other factors not captured in this study. The findings are consistent with those of Malek, Mearns and Dahlan A. Malek, Mearns, & Flin (2010) who found that hierarchical moderated multiple regression can be used to find out whether two sets of independent variables contributes to an increase in dependent variable by testing for changes in R square. Multiple regression has shown that openness, autonomy, integration and experimentation capacities have a significant influence on IP (Chang, Chang, Chi, Chen, & Deng, 2012).…”
Section: A Normality Test Of Ke and Ipsupporting
confidence: 90%
“…The original two-and three-factor structures provided by Warr et al (1979) were based on cluster analysis: an exploratory technique. These exploratory findings are still cited in contemporary literature (e.g., Falkum & Vaglum, 2005;Mohd Dahlan et al, 2010;Ose et al, 2010;Solberg et al, 2012;Travers & Cooper, 1993;Turner, Ross, & Ibbetson, 2011), most frequently with reference to the two-factor (intrinsic/extrinsic) solution. In terms of supplementary evidence of the scale's two-factor consistency, however, past findings have been limited.…”
Section: Structural Properties Of the Jssmentioning
confidence: 98%
“…Because of the broad applicability of the construct to a variety of organisational circumstances and paths of research inquiry, JS has been extensively linked to a multitude of constructs within the I/O psychology literature. Outcomes and antecedents such as employee affectivity (Dormann & Zapf, 2001), organisational commitment (Meyer & Allen, 1991;Meyer, Allen, & Smith, 1993), organisational culture (Balthazard, Cooke, & Potter, 2006;Bellou, 2010;Berson, Oreg, & Dvir, 2008;Cooper-Thomas, Van Vianen, & Anderson, 2004;Gregory, Harris, Armenakis, & Shook, 2009;Jandeska & Kraimer, 2005;Tzeng, Ketefian, & Redman, 2002;Yiing & Ahmad, 2009), workaholism (McMillan, Brady, O'Driscoll, & Marsh, 2002), stress and coping behaviour (Mohd Dahlan, Mearns, & Flin, 2010), and turnover intention (Seston, Hassell, Ferguson, & Hann, 2009) have been tied to the construct of JS. A metaanalysis on the correlates of JS by Faragher, Cass, and Cooper (2005) noted that depression, anxiety, burnout, and self-esteem were all moderately associated with JS.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Consequently, a growing number of companies, scientific resources, as well as business educators and practitioners have started to devote attention to the employees' psychological health [13,14]. Furthermore, a significant number of studies has been developed over the last forty years in several occupations [9], e.g., community health-care [15], police officers [16], firefighters [17], teachers [18], manufacturing workers [13] and correctional officers [19] across different countries. Aimed at helping professionals to comprehend its causes, the key relationships with outcomes that are essential to employees as well as organizational functioning and strategies to mitigate its pervasiveness [9,14].…”
Section: Introductionmentioning
confidence: 99%